2019
DOI: 10.11591/edulearn.v13i4.14353
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of think-pair-share to mathematics instruction

Abstract: The purpose of this research was to study the procedure of think pair share, the type of cooperative learning models, which can be implemented in mathematics instruction in Manokwari, West Papua Indonesia. This study was conducted at Senior High School in Manokwari (SMA Negeri 1), Manokwari West Papua Indonesia. The research was carried out using research and development methods. The Think Pair Share learning model was modified to get the procedure of implementation in accordance with the characteristics of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
2
6
0
1
Order By: Relevance
“…Think Pair and Share type learning examines students to explore individual and group thoughts on the topic of classification material for organism things and guides students to think broadly in discussions to share knowledge with other students. This is in line with the results of research from [11] where discussions in an active learning process can help improve the character of students or students become more independent in finding and managing information about the material learned to learn. Activeness in student discussion can make students better at interacting between students because students can apply their knowledge to share with other students, this can help support the development of student learning outcomes…”
Section: Resultssupporting
confidence: 85%
“…Think Pair and Share type learning examines students to explore individual and group thoughts on the topic of classification material for organism things and guides students to think broadly in discussions to share knowledge with other students. This is in line with the results of research from [11] where discussions in an active learning process can help improve the character of students or students become more independent in finding and managing information about the material learned to learn. Activeness in student discussion can make students better at interacting between students because students can apply their knowledge to share with other students, this can help support the development of student learning outcomes…”
Section: Resultssupporting
confidence: 85%
“…Meanwhile, observations on student performance showed that students were more actively involved with the use of the T-P-S type of cooperative learning method. These results are consistent with Tanujaya and Mumu (2019) and suggest that group members should consist of students who already know each other well, but should not have the same level of knowledge, while the number of group members should start from two students.…”
Section: Observingsupporting
confidence: 86%
“…Tint and Nyunt (2015) add that the think-pair-share technique encourages learners to justify their mathematical ideas using clear examples, clarity of thought and expression and correct mathematics vocabulary. The technique gives learners time to think, respond and help each other (Lee, Li & Shahrill, 2018;Tanujaya & Mumu, 2019). This helps learners to improve their understanding of the learnt mathematics concepts and to build on other learners' opinions to strengthen their own (Kwok & Lau, 2015;Tint & Nyunt, 2015).…”
Section: Discussionmentioning
confidence: 99%